Family Life in Lockdown - Pietro Biroli; Steven J. Bosworth; Marina Della Giusta; Amalia Di Girolamo; Sylvia Jaworska; Jeremy Vollen (Institute of Labor Economics (IZA), 2020)
We present findings from a novel survey of Italian, British, and American families in lockdown during the COVID-19 pandemic of spring 2020. A high percentage report disruptions in the patterns of family life, manifesting in new work patterns, chore allocations and household tensions. Though men have taken a greater share of childcare and grocery shopping duties, reallocations are not nearly as stark as disruptions to work patterns might suggest, and families having to reallocate duties report greater tensions. Our results paint a picture of tightened constraints budging up against stable and gendered patterns of intra-household cooperation. While the long-run consequences of the COVID-19 lockdown on family life cannot be assessed at this stage, we point towards the likely opportunities and challenges.
Keywords: D13; J12; J22; 330; lockdown; care; housework; tensions; COVID-19